Mali : Requests for Disbursement Under the Rapid Credit Facility and Rephasing of Access Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report, 2020)
The COVID-19 pandemic has added to Mali's significant security and social challenges. The outbreak reached Mali relatively late, with first confirmed cases on March 24 and 293 cases (seventeen deaths) as of April 22, 2020. The authorities took early containment measures in March and announced a package of economic and social support measures in early April. Growth is expected to decelerate sharply in 2020 as a result of declines in travel, trade, FDI and remittances. Job losses, weak social safety nets amid high informality, food insecurity and a fragile health system will exacerbate social challenges. Lower economic activity and the policy response will exert significant pressures on the budget and the balance of payments, opening financing gaps of 2.9 and 3.1 percent of GDP, respectively.